Gratitude as Mood Mediates the Effects of a 6-Weeks Gratitude Intervention on Mental Well-Being: Post hoc Analysis of a Randomized Controlled Trial - Bohlmeijer, Ernst; Kraiss, Jannis; Schotanus-Dijkstra, Marijke; ten Klooster, Peter (Frontiers in Psychology, 2022)
There is a gap of knowledge about the extent to which gratitude is indeed the working mechanism of change in gratitude interventions aiming to promote mental well-being. This study explores the mediational role of gratitude as mood in the context of a recently conducted randomized controlled trial on the effects of a 6-week gratitude intervention on mental well-being in comparison with a waitlist control group. Gratitude as mood was measured at 2, 4 and 6 weeks. Both simple and multiple mediation models were conducted as well as various sensitivity analyses. Results showed a gradual increase of gratitude as mood during the intervention. The effects of the 6-week gratitude intervention on mental well-being were mediated by increases of gratitude as mood at 4 weeks but not at 2 weeks. These findings suggest a dose-response relationship for gratitude interventions, but more research is warranted.